Steel structure installation (frame structure) / Mohamad Nazrul Amir Zulkifli - Zulkifli, Mohamad Nazrul Amir (Universiti Teknologi MARA, Perak, 2021)
Structures are one of the essential structural elements of a building. A structure plays many functions in the performance of the building, and these functions need to be fully understood in order to create a strong and comfortable building as well as provide protection from wind load and earthquake. This report will discuss steel structure installation for the building frame structure. This report was conducted for The Construction of One Petrol Station involved of a fuel station, convenience store and TNB substation at Lot 110533 Kampung Cengal Lempung Mukim Sungai Karang Daerah Kuantan, Negeri Pahang that owned by Petron Corporation Malaysia. The objective of this report is to analyze the construction of steel structure and how it is carried out. It will focus on the whole process of steel structure installation. It also investigates the equipment and machinery in the methods of frame structure installation to determine the time that has been used for the construction. This report will also look at the problem and the solution in structure construction that would fulfil the criteria of steel structure. Finally, the consequences of this project will only provide benefits to the villagers as opposed to disadvantages.